Reliability of squat and countermovement jump tests in children 6 to 8 years of age - Acero, R. M.; Fernandez-del Olmo, M.; Sanchez, J. A.; Otero, X. L.; Aguado, X.; Rodriguez, F. A. (Pediatric Exercise Science, 2011)
The aim of this study was to determine the reliability of the squat jump test (SJ) and countermovement jump test (CMJ), in fifty-six children (30 girls and 26 boys) with ages ranging from 6 to 8 years. Each subject performed two evaluation sessions (T1, T2) with seven days between tests. The results show that the CMJ test has a high intratrial reproducibility in T1 and T2 measured through intraclass correlation coefficient (ICC => 0.95). The ICC for the SJ test had a high value (0.99) only in T1.The variability for both tests among children under 9 years of age is higher than those reported for adult subjects in other studies. The intersession reliability was questionable with a high methodical error (ME= 9.86-15.1%, for the SJ and CMJ, respectively) and a significant worsening of the results of CMJ in T2 (p < .05).